Gendering the nation: A case study on the postage stamps of Cyprus - Andreou, Sonia; Stylianou, Stephanie; Zantides, Evripides (My University, 2017)
The current study addresses the gender roles and the stereotypes produced in the context of Cypriot society, through their representations on postage stamps produced by the Republic of Cyprus from 1960 to 2013. The theoretical framework employed derives from relevant theories on social roles' divisions based on gender, as well as the way these roles and stereotypes are expressed through images. The corpus has been analyzed by means of content analysis and semiotic analysis was employed in order to explore how the theoretical framework complies with selected stamps from the content analysis in respect of non-verbal signs. According to the findings, the role of women on stamp representations seems to be secondary and tied with emotional qualities, while men seem to hold a more prominent position in the society. This fact is reflected both on the quantity of stamps representing each gender in the respective thematic categories, as well as, on the selected stamps studied with semiotic analysis. Nonetheless, there have been strong indications that the social roles of genders and therefore stereotypes have started changing as the society progresses through the years. This process however, does not seem apparent on the imagery used for the stamps of the Republic of Cyprus.
Keywords: Cultural; Cyprus; Gender representation; Postage stamps; Visual semiotics